Wearable sensors based gait acquisition For motion analysis and prosthetic Ankle-foot design - Negi, Sachin (IIT BHU Varanasi, 2022)
Abstract is available in the content
Keywords: Wearable sensors; gait acquisition; motion analysis and prosthetic; Ankle-foot design